Zuckerkandl tubercle in thyroid surgery: Is it a reality or a myth?. (May 2016) - Irkorucu, Oktay
Abstract: Background: Zuckerkandl tubercle (ZT) is a lateral projection from the lateral thyroid lobe which is a constant landmark for finding the recurrent laryngeal nerve during thyroid surgery. It is the condensed thyroid parenchyma located in the cricothyroid junction. Even today, ZT and its relationship with recurrent laryngeal nerve (RLN) is not well known by all surgeons. The objectives of the present study were to find out the incidence of ZT in our thyroidectomies and to investigate whether the ZT has a relationship with RLN. We also discussed how to prevent RLN injury during thyroidectomy. Materials and methods: One hundred operations were performed by the same surgeon included in this study. All operations performed with intraoperative neuromonitorization (IONM) for proving the visualization of RLN. In each patient, particularly the ZT and its relationship with RLN searched and recorded. We also analyzed the patients in terms of sex, age, clinical diagnosis, and types of performed operations. Results: In 100 operations, 173 thyroid lobectomies were considered. 87 of these lobectomies were in right side and 86 in left side. The ZT was determined in 127 of 173 (73.41%) lobectomies. ZT was detected in 68 (78.16%) of right thyroid lobes whereas in 59 (68.60%) of left thyroid lobes. We observed that the ZT was detected more frequently in the right side. In 115 (90.55%) of these occasions, the recurrent nerve was directed upwards covered by the ZT. Conclusions: If it is present, ZT is a real constant landmark pointing to the RLN. In order to find and protect RLN during thyroid surgery, a careful, bloodless, and meticulous dissection should be carried out around the ZT. Although our results are encouraging, further researches are still needed on this topic. Highlights: Zuckerkandl tubercle (ZT) is a lateral projection from the lateral thyroid lobe. Even today, ZT and its relationship with recurrent laryngeal nerve (RLN) is not well known by all surgeons. If it is present, ZT is a real constant landmark pointing to the RLN. In order to find and protect RLN during thyroid surgery, a careful dissection should be carried out around the ZT.